Research as Artisanship versus Research as Generation of Novelty: The March to Nowhere. Issue 4 (2nd October 2018) - Cropley, Arthur
Abstract : The desire to ensure that its findings stand up to scrutiny is leading to a redefinition of research as skilled application of special techniques rather than a search for fresh insights. Generating novelty is now being seen as dangerous, because it could lead to false conclusions and loss of public confidence. The remedy is said to be replicability. However, replicability is not the goal of research, but a criterion for testing the robustness of novel ideas. The real problem is not excessive focus on novelty, but the poor quality of public dissemination of research findings. Thus, what is needed are public education and a responsible role for the media in informing the public, not the self-imposition of stifling orthodoxy on research.